"From the technology came the idea": safe implementation and operation of a high quality teleradiology model increasing access to timely breast cancer assessment services for women in rural Australia - Karen Johnston; Deborah Smith; Robyn Preston; Rebecca Evans; Karen Carlisle; Janet Lengren; Helen Naess; Elizabeth Phillips; Greg Shephard; Lorraine Lydiard; Debbie Lattimore; Sarah Larkins (BMC, 2020)
Abstract Breast cancer is the most commonly diagnosed cancer in Australian women. Providing timely diagnostic assessment services for screen-detected abnormalities is a core quality indicator of the population-based screening program provided by BreastScreen Australia. However, a shortage of local and locum radiologists with availability and appropriate experience in breast work to attend onsite assessment clinics, limits capacity of services to offer assessment appointments to women in some regional centres. In response to identified need, local service staff developed the remote radiology assessment model for service delivery. This study investigated important factors for establishing the model, the challenges and enablers of successful implementation and operation of the model, and factors important in the provision of a model considered safe and acceptable by service providers. Methods Semi-structured interviews were conducted with service providers at four assessment services, across three jurisdictions in Australia. Service providers involved in implementation and operation of the model at the service and jurisdictional level were invited to participate. A social constructivist approach informed the analysis. Deductive analysis was initially undertaken, using the interview questions as a classifying framework. Subsequently, inductive thematic analysis was employed by the research team. Together, the coding team aggregated the codes into overarching themes. Results 55 service providers participated in interviews. Consistently reported enablers for the safe implementation and operation of a remote radiology assessment clinic included: clinical governance support; ability to adapt; strong teamwork, trust and communication; and, adequate technical support and equipment. Challenges mostly related to technology and internet (speed/bandwidth), and maintenance of relationships within the group. Conclusions Understanding the key factors for supporting innovation, and implementing new and safe models of service delivery that incorporate telemedicine, will become increasingly important as technology evolves and becomes more accessible. It is possible to take proposed telemedicine solutions initiated by frontline workers and operationalise them safely and successfully: (i) through strong collaborative relationships that are inclusive of key experts; (ii) with clear guidance from overarching bodies with some flexibility for adapting to local contexts; (iii) through establishment of robust teamwork, trust and communication; and, (iv) with appropriate equipment and technical support.